Echocardiographic findings in prolapsed aortic cusp with vegetation. - Shiu, M F (1979)
A patient with severe aortic regurgitation showed abnormal echoes in the left ventricular outflow tract compatible with aortic vegetation or flail aortic cusp. At operation, a pedunculated vegetation on a prolapsed aortic cusp was found. The case illustrates some of the pitfalls in the echocardiographic distinction of the two conditions.